Turbulence Scale Characteristics in a Patchy Vegetated Open Channel - O. P. Folorunso (Archives of Current Research International, 2018)
Experiments were conducted to determine the turbulent scale characteristics in a Patchy vegetated channel with gravel bed. The analyses include the autocorrelation functions and integral length scales of turbulent energy. The general trend in the integral length scale is an increase in depth with large variations around this trend, however, the large variation indicates vortex stretching and the corresponding interaction thereof with other eddies. The results suggest that sizes of vegetation stems are likely to play a large part in the sizes of eddy formation, hence generating eddies with a length scale similar to the size of the vegetation stems. However, it is possible to deduce that the eddy generated encounters the size of the roughness elements creating them. Hence, higher time scale over the gravel bed suggests longer turbulence connection relative to the vegetated bed.